2011
DOI: 10.5897/sre11.777
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some process variables on zinc coated low carbon steel substrates

Abstract: This work investigates the effect of some essential plating variable of zinc electro-deposition on low carbon steel substrates. The variation of plating parameter, the depth of immersion, distance between the anode and the cathode on voltage, plating time and coating thickness was considered. The steel substrates were immersed into solution of zinc electroplating bath for varying voltage between 0.5 and 1.0 V. It was discovered that the sample plated at 0.8 V for 20 min gave the best plating properties and it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 4 publications
2
18
0
Order By: Relevance
“…This characterization is in line with the obtained results by [12,13] that particle agglomeration occurs when greater attraction than repulsion energy exists between them. Secondly, there is likely oxide growth at the surface of the metal due to the interaction of Zn with O 2− or OH − anions [1,17].…”
Section: Sem/eds Structural Studiessupporting
confidence: 80%
See 1 more Smart Citation
“…This characterization is in line with the obtained results by [12,13] that particle agglomeration occurs when greater attraction than repulsion energy exists between them. Secondly, there is likely oxide growth at the surface of the metal due to the interaction of Zn with O 2− or OH − anions [1,17].…”
Section: Sem/eds Structural Studiessupporting
confidence: 80%
“…Effort to strengthen this atmospheric, high temperature corrosion and mechanical deformation on most fabricated components, moving vessels and equipment is thus a concern of recent [7,8]. Alloy development with thin film codeposition for the purpose of combating high temperature corrosion and improved mechanical value is now gaining ground [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical behaviour due to thermal treatment and porosity within the alloy surface could results in hardness distribution. Some literatures also agree to the fact that compression stress could significantly perk up the micro-hardness when it is much less than the ultimate strength of the coating but [14] revealed that the flaws such as porosity, macro-particle at the alloy surface will have unfavourable effect on the mechanical properties. The Figure 7 also compares the hardness properties of the composite coatings before and after thermal treatment.…”
Section: Microhardness Studymentioning
confidence: 97%
“…Lately, major efforts to improve the wear, hardness and corrosion resistance of metallic zinc coating, can be traced towards its composites with different materials [11][12][13][14][15][16][17][18]. It is also identified, in particular, that the physical, mechanical and electrochemical properties of materials can be improved with the introduction of nano powders as the second phase particles within the material of interest [13][14][15][16][17][18]. Due to this improvement, composites and alloys such as Zn-Al2O3, Zn-WO3, Zn-Al and Zn-Ni have tremendously gained a wider range of applications in both marine and manufacturing industries recently as a better alternative for regular zinc plating [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, their susceptibility to corrosion, poor tribological resistance and low hardness limit their applications [2,3]. Nevertheless, many surface enhancement techniques such as thermal spray, vapor deposition, laser alloying, galvanizing and painting have been adopted to improve mild steel properties against electrochemical reaction and plastic deformation [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%